INTEGRATED ANALYSIS OF THE EFFICACY AND FUNCTIONAL BENEFITS OF COMPRESSION-BASED TREATMENTS FOR CHRONIC VENOUS INSUFFICIENCY (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This comprehensive thesis provides an in-depth analysis of compression therapy products used in the treatment of varicose veins and chronic venous insufficiency. The research employs a systematic literature review methodology to evaluate the multifaceted benefits of these medical textiles, focusing on their biomechanical properties, material composition, and clinical effectiveness. The study reveals that the therapeutic value of compression garments is directly determined by their engineering characteristics, including compression class specifications, elastic properties, and durability parameters. Our findings demonstrate that optimal patient outcomes are achieved through precise matching of product specifications with individual pathological requirements. The thesis also explores future directions in smart textile technology and personalized treatment approaches, offering valuable insights for clinicians, researchers, and medical textile manufacturers working in vascular health management.